Cooper-pair splitting in two parallel InAs nanowires. (15th June 2018) - Baba, S; Jünger, C; Matsuo, S; Baumgartner, A; Sato, Y; Kamata, H; Li, K; Jeppesen, S; Samuelson, L; Xu, H Q; Schönenberger, C; Tarucha, S
Abstract: We report on the fabrication and electrical characterization of an InAs double-nanowire (NW) device consisting of two closely placed parallel NWs coupled to a common superconducting electrode on one side and individual normal metal leads on the other. In this new type of device we detect Cooper-pair splitting (CPS) with a sizeable efficiency of correlated currents in both NWs. In contrast to earlier experiments, where CPS was realized in a single NW, demonstrating an intrawire electron pairing mediated by the superconductor (SC), our experiment demonstrates an interwire interaction mediated by the common SC. The latter is the key for the realization of zero-magnetic field Majorana bound states, or Parafermions; in NWs and therefore constitutes a milestone towards topological superconductivity. In addition, we observe transport resonances that occur only in the superconducting state, which we tentatively attribute to Andreev bound states and/or Yu-Shiba resonances that form in the proximitized section of one NW.